H25 The social and educational impact of attending an huntington's disease specific camp. (September 2018) - Swope, Chandler; Martin, Catherine; Ellison, Matthew
Abstract : Background: There are many camps available to support young people who are currently suffering from symptoms from an illness or condition, but little availability of camps for those with parents suffering from an illness where the young people are at risk for developing the same illness. The Huntington's Disease Youth Organization (HDYO) has hosted eight camps around the world over the course of five years for young people impacted by HD. The aim of these camps is to provide the camper respite, a space for peer and professional support as well as access to education that is age and stage appropriate. Case history: Campers overwhelming spoke to camp helping them feel less isolated and more in control of their journey with HD. Over 50% of campers in our study (only 10 campers completed all pre and post surveys) stated they had more specific knowledge about HD, there was also a statistically significant increase in the campers sense of social support and an increase positive sense of self-esteem (Kavanaugh et al, 2017). Conclusion: There is still limited data on camps for young people at-risk of HD, but early information points to the existence of these camps to be hugely important for healthy outcomes. Furthermore, feeling educated about the disease, and research leads to young people feeling empowered and less afraid of the disease. They can also get practical information to help them make critical decisions (testing, family planning, symptom management etc) for their own journey with HD.